Epidemiology of Kawasaki Disease in South Korea: A Nationwide Survey 2015–2017. Issue 11 (November 2020) - Kim, Gi Beom; Eun, Lucy Youngmin; Han, Ji Whan; Kim, Sung Hye; Yoon, Kyung Lim; Han, Mi Young; Yu, Jeong Jin; Choi, Jong-Woon; Rhim, Jung Woo
Abstract : Background: This study aimed to investigate recent epidemiologic features of Kawasaki disease (KD) in South Korea. Methods: The ninth triennial nationwide questionnaire survey collected data on the demographic findings, symptoms and signs, treatment patterns and coronary artery complications of acute-phase KD occurred in 2015–2017 from 98 hospitals with pediatric residency programs and 108 community hospitals without residency programs. Results: We received data from 93 of the 98 hospitals (response rate: 94.9%) with residency programs and 75 of the 108 community-based children's hospitals (response rate: 69.4%) without residency programs. In the 3-year survey period, a total of 15, 378 (5449 in 2015, 5171 in 2016 and 4758 in 2017) cases of KD were reported. The mean age at diagnosis was 33.0 ± 24.8 months (range: 0–205 months), and the male-to-female ratio was 1.41:1. The overall KD incidence was 196.9 (202.2 in 2015, 197.1 in 2016 and 191.0 in 2017) per 100, 000 younger than 5 years population. Recurrent cases were 4.85%. KD occurred more frequently during winter (December–January) and late spring (May–June). Intravenous immunoglobulin (IVIG) was administered to 95% of the patients; nonresponder rate for the first IVIG was 14.8%. Coronary artery aneurysms and giant coronary artery aneurysms (internal diameter >8 mm) occurred in 1.7% and 19 patients, respectively. Two patients died due to multiorgan failure and hepatic encephalopathy. Conclusion: Peak incidence of KD in South Korea was 202.2 per 100, 000 younger than 5 years population (2015), and the incidence of giant coronary artery aneurysm decreased to 0.09% (2017). Abstract : Supplemental Digital Content is available in the text.